Job Turnover, Unemployment and Labor Market Institutions - Gilles Joseph; Olivier Pierrard; Henri R. Sneessens (Institute for the Study of Labor (IZA), 2003)
This paper studies the role of labor market institutions on unemployment and on the cyclical properties of job flows. We construct an intertemporal general equilibrium model with search unemployment and endogenous job turnover, and examine the consequences of introducing an unemployment benefit, a firing cost and a downward wage rigidity. The model is able to reproduce the main cyclical properties of a typical European economy. It also suggests that downward wage rigidities, rather than unemployment benefit or firing cost, may well play a dominant role in explaining both the high unemployment rate and the cyclical properties of such an economy.
Keywords: J65; E24; J63; J38; 330; unemployment; job flows dynamics; institutions; Arbeitsmobilität; Konjunkturelle Arbeitslosigkeit; Theorie der Arbeitslosigkeit; Arbeitsuche; Arbeitslosenversicherung; Kündigungsschutz; Lohnrigidität; Theorie